Studies on Argentinean species of the Bahitini leafhopper genus Menosoma Ball, 1931 (Hemiptera: Cicadellidae); checklist, key to known species, and redescription of Menosoma taeniatum Linnavuori with a new country record - Pinedo-Escatel, J. A.; Becerra-Chiron, I. M.; Torres-Moreno, R. (Zootaxa, 2023)
The species of the genus Menosoma to occur in Argentina are revised. Menosoma taeniatum Linnavuori is redescribed using recent samples taken from Northeast Argentina. Overall habitus images of external and internal morphology are provided. In addition, a new country record is reported for Bolivia. An updated checklist and key to all Menosoma species known to occur in Argentina are also given.